Evaluating the Amuay Refinery main catalytic cracking unit fractionator - Cabrera, Ebert; Bitter, Augusto; Sánchez, Jorge (Revista Técnica da Faculdade de Engenharia da de Zulia, 1970)
The catalytic cracking unit in Lagoven's Amuay Refinery (Falcón, Venezuela) was started up in May 1991 after a revamping project to increase the unit capacity to 645 t/h (108 KBD). Signs of flooding were noticed in the fractionator, trays, such as sudden increases in pressure drops and variations in product flow. On several occasions, feeding had to be reduced to 615 t/h. The fractionator was simulated in order to study the cause of these problems and identify the process and hydraulic limitations that cause such unstabilities when 645 t/h are fed to the fractionator. PRO II, Version 3.3, was used to simulate the fractionator and standard correlations were used for hydraulic evaluation. It was found that the fractionator is hydraulically limited by high vapor loads. As a result, there is no flexibility to accommodate operational peeding changes. Some adjustments of the operation conditions and replacement of some trays with structured packing are recommended to improve fractionator operation.